The Brasilian rural education analyzed by Lourenço filho in the early 1960s - Filho, Macioniro Celeste [UNESP] (FapUNIFESP (SciELO), 2019)
Lourenço Filho was one of the most important intellectuals to influence the direction of Brazilian education in the 20th century. In the 1950s and 1960s, working in international organizations such as the Organization of American States (OAS), he analyzed the trajectory of rural education in the Americas. In 1962, Lourenço Filho wrote a study for the OAS on rural education, which was not published in Brazil. It is the purpose of the present work to present what this intellectual approached Brazilian rural education in this text sent to the OAS. The methodology used was the documentary analysis on the text of Lourenço Filho. The objective is to present the unpublished contribution in Brazilian publications of this author when dealing with rural education in the early 1960s.
La educación rural Brasileña analizada por Lourenço filho a pricipios de la década de 1960
L'Éducation rurale Brésilienne analysée par Lourenço filho au début des années 1960
Keywords: Lourenço Filho; Organization of American States; Rural education